Antagonistic interactions between maize seeds microbiome species and the late wilt disease agent, Magnaporthiopsis maydis - Degani, Ofir; Ayoub, Aseel; Dimant, Elhanan; Gordani, Asaf (Frontiers in Fungal Biology, 2024)
Magnaporthiopsis maydis is a maize pathogen that causes severe damage to commercial corn fields in the late growth stages. Late wilt disease (LWD) has spread since its discovery in the 1960s in Egypt and is now reported in about 10 countries. The pathogen has a hidden endophytic lifecycle in resistant corn plants and secondary hosts such as foxtail, watermelon lupin and cotton. At the same time, it could be an opportunist and hinder the host development under the right conditions. This study uncovered M. maydis interactions with newly identified maize endophytes. To this end, six fungi were isolated from the seeds of three sweet corn cultivars having varying susceptibility to LWD. These isolates were identified using colony morphology and microscopic characterization, universal internal transcribed spacer (ITS) molecular targeting and phylogenetic analysis. Most of them belonged to pathogenic species. Compared to three previously identified bioprotective microorganisms, the new species were tested for their ability to secrete metabolites that repress M. maydis in vitro and to antagonize it in a solid media confront test and a seedlings pathogenicity assay. The opportunistic fungal species Aspergillus flavus (ME1), Aspergillus terreus (PE3) and the reference biocontrol bacteria Bacillus subtilis (R2) achieved the highest M. maydis inhibition degree in the plates tests (74-100% inhibition). The seedlings' pathogenicity assay that predicts the seeds' microflora resistance to M. maydis highlighted the bio-shielding potential of most species (23% or more epicotyl elongation over the infected control). Fusarium sp. (ME2) was the leading species in this measure (43% enhancement), and B. subtilis gave the best protection in terms of seeds' germination (50%) and sprouts' biomass (34%). The results of this study could enhance our understanding of the pathobiome's role in the context of LWD and represent a first step in using the seeds' natural protective microflora to develop novel management strategies.